2022
DOI: 10.3390/children9030308
|View full text |Cite
|
Sign up to set email alerts
|

Supracondylar Fractures of the Humerus: Association of Neurovascular Lesions with Degree of Fracture Displacement in Children—A Retrospective Study

Abstract: Supracondylar humerus fractures (ScHF) account for 60% of fractures of the elbow region in children. We assessed the relationship between neurovascular complications and the degree of fracture displacement as rated on the basis of modified Gartland classification. Moreover, we aimed to evaluate predisposing factors, e.g., age and gender, and outcomes of neurovascular complications in ScHF. Between 2004 and 2019, we treated 329 patients with ScHF at the Department of Traumatology and Orthopedics of the Upper Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 35 publications
2
13
0
1
Order By: Relevance
“…However, the indication for CT angiography is still debated and should not delay fracture reduction [ 27 ]. Tomaszewski et al reported good clinical results for children with SCHF and vascular injury at the one-year follow-up [ 12 ], which is in line with our study data. Our study demonstrates mostly excellent clinical outcomes at mid-term follow-up.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, the indication for CT angiography is still debated and should not delay fracture reduction [ 27 ]. Tomaszewski et al reported good clinical results for children with SCHF and vascular injury at the one-year follow-up [ 12 ], which is in line with our study data. Our study demonstrates mostly excellent clinical outcomes at mid-term follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…Differences between these numbers and those reported in the current study may be attributable to selection bias—the interest in the current studs was the operatively managed fracture population. The indication to operative management is directly related to fracture displacement, which has an inherently higher risk of neurovascular injury [ 12 , 13 ]. Interestingly no correlation was identified between neurological injury and the number or location of K-wires.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The management of SCHF with vascular or nerve injury remains debated, perhaps due to their relative infrequency and concerns about the long-term sequelae in this subset of patients. Median nerve injuries complicate ~5% to 10% of SCHF, occurring most commonly in extension-type fractures 1–4 . Several studies have evaluated the management of SCHF with vascular compromise, with or without nerve involvement, but few have focused specifically on SCHF-induced median nerve injury.…”
mentioning
confidence: 99%